Higher Levels of Cytokines in Patients with Chronic Limb-Threatening Ischemia - Ferreira, Joana; Roque, Susana; Longatto-Filho, Adhemar; Afonso, Julieta; Carneiro, Alexandre; Vila, Isabel; Silva, Cristina; Cunha, Cristina; Mesquita, Amílcar; Cotter, Jorge; Correia-Neves, Margarida; Mansilha, Armando; et al. (Annals of vascular surgery, 2024)
Inflammation is a key element in the initiation and progression of peripheral arterial disease (PAD). Understanding the impact of inflammatory molecules, as cytokines in PAD could help us to improve the prognosis of these patients. The main goal of this study was to compare the serum level of cytokines between patients with claudication to those with chronic limb-threatening ischemia (CLTI). The second objective was to evaluate the relationship between the levels of cytokines and death or amputation rate. An observational, single-center, and prospective study was conducted from January 2018 to July 2022. The study was approved by the ethical commission of the Local Hospital (75/2017). Patients with PAD, suggested by the clinical history and objective examination and confirmed with ankle-brachial index, attending vascular surgery consultations of the first author were included. The following exclusion criteria were applied: i) bedridden individuals or subjects who refused to participate in the protocol; ii) diseases responsible for body composition changes or proinflammatory state; iii) recent diet change, iv) active malignancy, v) autoimmune disease, vi) active infection, vii) chronic renal failure (glomerular filtration rate <30 mL/min/1.73 m2), or viii) heart failure in the past 3 months. This cohort was observed at admission, 3, 6, and 12 months. A panel of 27 cytokines was determined with ELISA, at baseline. We included 119 subjects (mean age: 67.58 ± 9.60 years old; 79.80% males), 65 patients with claudication and 54 with CLTI. From the 27 cytokines analyzed, patients with CLTI, when compared to those with claudication, had a higher serum level of 11 cytokines: IL1ra, IL-6, IL-8, IL12 p70, G-CSF, IP-10, MCP-1, MIP-1α, PDGF-β, RANTES, and TNF-α. From the group of patients with CLTI those who underwent a major amputation had a higher serum level of FGF-basic [median = 49.04; interquartile range = 37.03–52.49; versus median = 33.04; interquartile range = 28.60–38.98; P = 0.001]. Patients with CLTI have higher serum level of inflammatory cytokines, which may have role in the prognosis of these patients.